2018
DOI: 10.4314/agrosh.v18i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maize production on poverty alleviation of farmers in Edo state, Nigeria

Abstract: The high incidence of poverty in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The effects of maize production on income generation of maize farmers are enormous. Ahmadu and Edeoghon (2018) found that the most important benefit from maize was rare cases of hunger in the respondents' family. Maize contributes significantly to average annual food production, total food availability, caloric intake and total food demand among households in Nigeria…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of maize production on income generation of maize farmers are enormous. Ahmadu and Edeoghon (2018) found that the most important benefit from maize was rare cases of hunger in the respondents' family. Maize contributes significantly to average annual food production, total food availability, caloric intake and total food demand among households in Nigeria…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, poverty is increasing despite the country's sixth position as the world's largest oil exporter. The incidence and depth of poverty over the past few decades in the country have continued to worsen (Ahmadu and Alufohai, 2011), becoming worse than the rates in most countries of the world (Kanayo, 2014) Poverty incidence in Benue State is very high. According to Global data Lab report for Benue State 2018, the percentage household International Wealth index (IWI) value (under 70) stood at 88.6, under 50 stood at 68.5 while under 35 stood at 43.8.…”
Section: Introductionmentioning
confidence: 99%
“…There are many research studies that addressed maize in Nigeria: but the focus is mainly on nutrient uptake, the performance of the maize crop (Ekesiobi et al, 2015 andAderibigbe et al, 2017), the resource-use efficiency (Oluwatayo et al, 2008, Kasim et al, 2014, alleviation of poverty (Oladeebo et al, 2017 andAhmadu andEdeoghon, 2018), and chemical and nutritional analysis (Sule et al, 2014). Other research that address poverty include: Anowor et al 2013 conducts a study to evaluate the role of agriculture in poverty alleviation, Aigbokhan (2008) studies growth, inequality and poverty in Nigeria, Iheke and Arikaibe (2012) evaluate the impact of agricultural intensification on poverty alleviation in Nigeria, Ogundipe et al, (2016) examine the impact of agricultural productivity on downscaling poverty, , Eseyin et al (2016) investigate the effects of investments in the agricultural sector on poverty reduction in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The dwindling economy and widespread poverty in Nigeria and most developing countries of the world (Ahmadu and Alufohai, 2011;National Bureau of Statistics, 2012) call for a search for a business enterprise and a source of income whose investment capital in terms of finance, human resources, time and space is relatively low and affordable. Snail production fits perfectly into these requirements because the capital outlay for snail production is affordable, relatively cheap to start and manage when measured against its productivity, returns and other livestock (Ahmadu and Ojogho, 2012).…”
Section: Introductionmentioning
confidence: 99%